개발도상국 맞춤형 정수처리를 위한 수중 이온물질 제거용 이온교환섬유 성능평가에 관한 연구 - 여인설; 조은영; 박재로; 오현제; 이성재; 박찬규 (한국수처리학회지, 24(2), 2016)
In case of developing countries, the amount of available water resources is lacking compared to the population distribution. In addition, since they have relatively low economic level, environmental awareness and a lot of outdated facilities, it is important to introduce appropriate technology without a large cost to purify. In this study based on the preceding experiment it was performed to evaluate the performance of the ion exchange module for application of customized water treatment system in developing countries. All tests were conducted in a batch test that evaluates the adsorption properties, removal efficiency with different dosage, removal efficiency depending on time variation, interference effects and renewable experiment. Experimental results in terms of changing the dose of the ion exchange fiber tended to match generally the Langmuir adsorption isotherm that is based on monolayer adsorption. When the media dose was increased above 2 g/L, it is possible to remove the high concentration of contaminants. In addition, ionic contaminants from aqueous system has been removed generally in a short time and efficiently removed without interference effects. When using a NaCl solution, it was confirmed that regeneration is possible. KCI Citation Count: 0